PENGGUNAAN MEDIA WORD WALL UNTUK MENINGKATKAN KEMAMPUAN MENULIS TEGAK BERSAMBUNG (Studi Single Subject Research Pada Siswa Tunarungu Kelas III Di SKh Negeri 02 Kota Serang Banten ) - Hamdan Bachry; Dr. Joko Yuwono, M.Pd; Yuni Tanjung Utami, M.Pd (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2018)
This research aims to find out the influence of using Word Wall media to increase writing upright letter ability toward the deaf student at the third grade of SDLB SKhN 02 Serang Banten. This research use the experimental design that was the Single Subject Research (SSR) with A-B-A as reseach design. The subject of the research was one of the deaf students in the third grade. The condition of the research subject was less comprehend toward writing upright letter lesson. The data collecting methods were using tests, observation and documentation. The data obtained were analyzed using descriptive statistics then displayed in the form of tables and graphs. The results showed that the average percentage of baseline I 44%,with stability 86%, interpensi 71%, 80% stability and baseline II 53%, with the stability of 97%. It showed that the effect of Word Wall media positive towards improving the deaf student’s writing Upright letter ability.